We Don’t Need No Education (London Journal of Research In Humanities and Social Sciences, 2023)
The foundation of this paper is the premise that mankind is a result of evolution. From this requirement I conclude that every property of people must be generated by evolution. Here I justify that some social behavior must be innated. Education is not necessary to explain it. Of course, I can not prove that humans are generated by evolution.
Keywords: COVID-19; SARS-CoV-2; Modelling; Self-care